Potential Challenges in Logistics Outsourcing and their Impact on Supply Chain Management - Aleem, Syed Waqas; Asim, Muhammad; Manzoor, Salman (Journal of Quantitative Methods, 2025)
Logistics outsourcing is one of the common practices of the Supply Chain Management (SCM) and has proven to be effective to build competitive advantages in organizations. The academic literature has contributed to the effectiveness of logistics outsourcing in SCM. However, few studies have addressed the potential challenges faced in effective implementation of the relationship. Therefore, the current study aimed to address the challenges involved in logistics outsourcing and investigated the extent to which these challenges effect supply chain performance. The results revealed that challenges of warehousing, outsourcing inefficiency, and accountability significantly affect supply chain performance of food industries in Karachi. However, loss of control and security and track and trace gaps does not have a significant effect on supply chain performance. This indicates that industries should have a special focus on the challenges of warehousing, efficiency of outsourcing, and accountability in logistics outsourcing.